2016
DOI: 10.1016/j.ijnurstu.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative nurse-led self-management support for primary care patients with anxiety, depressive or somatic symptoms: Cluster-randomised controlled trial (findings of the SMADS study)

Abstract: A complex, nurse-led intervention, implemented as a collaborative care model, increased perceived self-efficacy in patients with symptoms of anxiety, depression or somatisation compare to control patients. For the first time in the German healthcare system, the SMADS trial validated the belief that a nurse can successfully complement the work of a general practitioner - particularly in supporting self-management of patients with psychosomatic symptoms and their psychosocial needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
4
36
0
5
Order By: Relevance
“…These findings align with the recovery approach in mental health, which involves people making sense of their experiences in a way that allows them to maintain a sense of personal efficacy or control (Chambers et al, 2015;Turner et al, 2015). In addition, each of these studies highlighted the need for health professionals to encourage individuals to take active roles in self-managing their mental and physical health (Chambers et al, 2015;Turner et al, 2015;Van Grieken et al, 2013;Zimmermann et al, 2016). Thus, the process of managing depression typically commences with seeking a diagnosis (Atkins, Naismith, Luscombe, & Hickie, 2015).…”
Section: Introductionmentioning
confidence: 55%
“…These findings align with the recovery approach in mental health, which involves people making sense of their experiences in a way that allows them to maintain a sense of personal efficacy or control (Chambers et al, 2015;Turner et al, 2015). In addition, each of these studies highlighted the need for health professionals to encourage individuals to take active roles in self-managing their mental and physical health (Chambers et al, 2015;Turner et al, 2015;Van Grieken et al, 2013;Zimmermann et al, 2016). Thus, the process of managing depression typically commences with seeking a diagnosis (Atkins, Naismith, Luscombe, & Hickie, 2015).…”
Section: Introductionmentioning
confidence: 55%
“…In contrast, it might be important to strengthen and to expand formal and informal networks as well as systematically and o cially include allied health professionals into structured care pathways. For instance, a model programme in Baden Württemberg, Germany, successfully implemented interprofessional quality circles that subsequently increased collaboration and networking (29), or collaborative nurse-led self-management support for primary care patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses play an integral role in patient care, and research has shown that nurse‐led care significantly and positively impacts the self‐efficacy of depressed patients (Zimmermann et al, ). Given the importance of mental health and psychiatric nurses in mental health care, additional tools and conceptual models can help support their important role in care and facilitate positive patient outcomes.…”
Section: Implications For Psychiatric and Mental Health Nursesmentioning
confidence: 99%